Optimal COVID-19 vaccine prioritization by age depends critically on inter-group contacts and vaccination rates - Iker Atienza-Diez; Gabriel Rodriguez-Maroto; Saúl Ares; Susanna Manrubia (Royal Society Open Science)
The limited availability of COVID-19 vaccines has prompted extensive research on optimal vaccination strategies. Previous studies have considered various non-pharmaceutical interventions, vaccine efficacy and distribution strategies. In this work, we address the combined effects of inter-group contacts and vaccination rates under contact reduction, analysing the Spanish population’s demographic and age group contact patterns and incorporating reinfection dynamics. We conduct an exhaustive analysis, evaluating 362 880 permutations of nine age groups across six vaccination rates and two distinct, empirically quantified scenarios for social contacts. Our results show that at intermediate-to-high vaccination rates with unrestricted social contacts, optimal age-based vaccination strategies only slightly deviate from older-to-younger prioritization, yielding marginal reductions in deaths and infections. However, when significant reductions in social contacts are enforced—similar to the lockdowns in 2020—there are substantial improvements, particularly at moderate vaccination rates. These restrictions lead to a transition where infection propagation is halted, a scenario that became achievable during the pandemic with the observed vaccination rates. Our findings emphasize the importance of combining appropriate social contact reductions with vaccination to optimize age-based vaccination strategies, underscoring the complex, nonlinear dynamics involved in pandemic dynamics and the necessity for tailored context-specific interventions.